Dry eye disease and pterygium - Baig, Munir Amjad; Munir, Rabeeya (Pakistan Journal of Ophthalmology, 2020)
Pterygium is a common external eye disease in general population which progresses slow but has a little effect on vision. Purpose: To know the tear film and ocular surface changes with pterygium. Study Design:A descriptive cross sectional study Place and duration of study: Federal Government Services Hospital Islamabad during Jun.2013 to Dec. Material and methods:Dry eye questionnaire (DEQ-6) was administered by a trained researcher and DE tests were performed in all 256 willing subjects (136 with pterygium+120control) age 30-76years,by a single surgeon under same physical conditions after taking the consent and approval from Hospital Ethical committee. Diagnosis was made on presence of both symptoms and tear film parameters. Statistical analysis was by simple percentages. Results:DE was found in 73(53.7%) of the pterygium cases and 28(23.5%) of the normal patients. In this study, 55(40.5%) were symptomatic, defined as reporting 1 or more DE symptoms often or all of the time. 53(39%) showed corneal fluorescein staining CFS and 69(51%) showed lid plugging/mucous threads in both groups Of 136 eyes with pterygium, [male 91 (67%) female 45(33%)], 50(37.5%) showed normal tear film and 86(62.5%) showed deranged functions whereas among 120 control eyes,[Male 73(61%) female 47(39%)],86(72.3%) were normal and 34(27.7%)had abnormal functions.These values were reduced indicating changed tear film in these patients. Conclusion:Pterygium disturbs tear functions causing dry eye like symptoms. Key-words: Dry eye, pterygium, tear film instability, ocular surface